Influence of different morphology of carbon nanostructures on the structural and optical properties of decorated single crystalline hematite nanocubes for photoelectrochemical applications - Rashid, Nur Maisarah Abdul; Talik, Noor Azrina; Chiu, Wee Siong; Sim, Khiew Poi; Nakajima, Hideki; Pan, Guan Ting; Yang, Thomas C.-K.; Rahman, Saadah Abdul (Elsevier, 2019)
Hematite (α-Fe2O3) is among one of the potential n-type metal oxide semiconductors that able to absorb wide range of visible spectrum and thus makes it a particularly attractive material to be used in solar energy conversion. In this work, facile hydrothermal approach was adapted to synthesis hybrid single crystalline cubic hematite decorated carbon nanostructures (α-Fe2O3/CNs) nanocomposites for photoelectrochemical (PEC) application. By harnessing the highly-exposed nature of CNs, it was used as a basal structure to anchor α-Fe2O3 semiconductor materials for enhanced light trapping to produce better PEC performance. α-Fe2O3 nanocubes were decorated on different CNs surface morphologies (namely globular- like CNs, caterpillar-like CNs, clustered caterpillar-like CNs, and granular-like CNs). High-resolution transmission electron microscopy reveals α-Fe2O3 were randomly distributed throughout the surface of CNs. Appreciating the unique structure of those hybrid nanostructures, the as-prepared hybrid α-Fe2O3/CNs nanocomposites exhibit improved light absorption and lower photocurrent onset potential as compared to pure CNs. The photocurrent density was determined to be in the range of 0.0199 to 0.1845 mA/cm2 at 1.23 V, where the α-Fe2O3/clustered caterpillar-like CNs showed the highest photocurrent density. Current study is believed to contribute to the field of materials science, particularly on the aspect of hybrid nanocomposites synthesis and PEC applications. © 2019 Elsevier B.V.